PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2012 - Ermi Astutik, 10.05.52.0007; Nurhayati, Ida (Students Journal of Accounting and Banking, 2014)
This study aimed to examine the effect of corporate governance mechanisms on the financial performance of the company. Financial performance calculated using the ROE, while good corporate governance mechanism is determined by the audit committee variables, managerial ownership, institutional ownership, and proprsi independent board. The sample in this study are all companies listed on the Indonesia Stock Exchange in 2010-2012. The samples used were 240 companies per year were taken by purposive sampling. Methods of analysis of this study uses multiple regression and simple regression SPSS 19. These results indicate that the audit committee and a significant positive effecton financial performance, managerial ownership and no significant negative effecton the performance of financial, institutional ownership and a significant positive effect on financial performance, independent Commissioner and no significant negative effecton financial performance.Keywords: corporate goodÂ  governance, audit committee, managerial ownership, ownership instutisional, independent commissione